2019
DOI: 10.3389/fonc.2019.00254
|View full text |Cite
|
Sign up to set email alerts
|

Multigene Mutation Profiling and Clinical Characteristics of Small-Cell Lung Cancer in Never-Smokers vs. Heavy Smokers (Geno1.3-CLICaP)

Abstract: Objectives: Lung cancer is a heterogeneous disease. Presentation and prognosis are known to vary according to several factors, such as genetic and demographic characteristics. Small-cell lung cancer incidence is increasing in never-smokers. However, the disease phenotype in this population is different compared with patients who have a smoking history. Material and Methods: To further investigate the clinical and genetic characteristics of this patient subgroup, a cohort of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 38 publications
(40 reference statements)
0
30
2
Order By: Relevance
“…Additionally, we identified a previously reported relationship between SMAD4 and carboplatin. Mutations in the SMAD4 gene have been linked to resistance of platinum-based drugs like carboplatin 15 , 16 , and our data suggest that head and neck cancer patients on carboplatin stratified by pre-treatment SMAD4 expression have significantly differential survival between the strata (Fig. 3 D).…”
Section: Resultsmentioning
confidence: 62%
“…Additionally, we identified a previously reported relationship between SMAD4 and carboplatin. Mutations in the SMAD4 gene have been linked to resistance of platinum-based drugs like carboplatin 15 , 16 , and our data suggest that head and neck cancer patients on carboplatin stratified by pre-treatment SMAD4 expression have significantly differential survival between the strata (Fig. 3 D).…”
Section: Resultsmentioning
confidence: 62%
“…In terms of clinical characteristics, several studies proposed that never-smoker SCLC was related to a female-gender predisposition. 33,34 In the study by Cardo et al the authors also found that SCLC patients with a smoking history presented with a higher incidence of brain metastasis, which might partly explain the poorer survival of smoker SCLC patients. 33 Overall, the mechanism behind the prognostic difference between smokers and never-smokers in SCLC still needs further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…However, the low frequency of clinically actionable driver mutations hinders the successful application of targeted therapies in SCLC. A difference in the mutational profile in SCLC according to the smoking status has also been reported (Cardona et al, 2019;Sun et al, 2015;Varghese et al, 2014). One study by Cardona et al demonstrated that EGFR, MET, and SMAD4 are more frequently mutated in never smokers, while RB1, CDKN2A, and CEBPA are more frequent in smokers (Cardona et al, 2019).…”
Section: Introductionmentioning
confidence: 95%